2020
DOI: 10.1177/0964528420912254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dry needling of active trigger points in the scalene muscles in individuals with mechanical neck pain: a randomized clinical trial

Abstract: Objective: The aim of this study was to compare the effects of dry needling (DN) versus pressure release over scalene muscle trigger points (TrPs) on pain, related disability, and inspiratory vital capacity in individuals with neck pain. Methods: In this randomized, single-blind trial, 30 patients with mechanical neck pain and active TrPs in the scalene musculature were randomly allocated to trigger point dry needling (TrP-DN; n = 15) or pressure release (n = 15) groups. The DN group received a single session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Three hundred and twenty-four ( n = 324) studies remained after removing duplicates. Two hundred and ninety-five ( n = 295) were excluded after the analysis of titles and/or abstracts, leaving 29 articles for final full-text review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. One article [ 34 ] was excluded because the comparator was acupuncture intervention and the placebo used laser.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three hundred and twenty-four ( n = 324) studies remained after removing duplicates. Two hundred and ninety-five ( n = 295) were excluded after the analysis of titles and/or abstracts, leaving 29 articles for final full-text review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. One article [ 34 ] was excluded because the comparator was acupuncture intervention and the placebo used laser.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen trials (53%, n = 15/28) reported information about adverse effects, with all of them reporting just minor events, and none reported any serious adverse effects [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 38 , 39 , 40 , 41 , 43 , 45 , 50 ]. Post-needling soreness was the most common adverse event and was reported in 53% (8/15) of the trials [ 27 , 28 , 32 , 38 , 40 , 43 , 45 , 48 ] and resolved spontaneously in 24–48h without further treatment. Thirteen (47%, n = 13/28) of the included studies [ 23 , 24 , 25 , 30 , 35 , 36 , 42 , 44 , 46 , 47 , 48 , 49 , 51 ] did not report any information about adverse events ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…While there was no difference between the groups after the treatment and at the first week of the treatment, it was observed that the dry needling treatment was superior in reducing the pain at the first month of the treatment. In addition, dry needling therapy was found to provide a greater increase in inspiratory vital capacity in all control periods compared to local pressure therapy 31 . Cerezo-Téllez E et al, in an article they published in 2016, investigated the effectiveness of dry needling in their study on office workers with neck pain.…”
Section: Dry Needling and Neck Painmentioning
confidence: 85%
“…Forty-two RCTs were rated as having a low risk of bias in random sequence generation: Of them, 26 [ 25 , 30 33 , 35 38 , 40 , 41 , 45 , 47 , 51 , 53 , 54 , 60 , 62 – 64 , 67 , 71 , 74 , 79 , 87 , 88 ] used various computerized randomization programs, 11 [ 43 , 44 , 50 , 55 , 58 , 66 , 68 , 72 , 78 , 81 , 85 ] used random number tables, 3 [ 27 29 ] used coin tossing, and 2 [ 24 , 39 ] used block randomization. In terms of allocation in the RCTs, 19 studies [ 24 , 26 , 30 32 , 38 41 , 45 , 58 , 62 , 64 , 67 , 71 , 79 , 84 , 87 , 88 ] described proper allocation concealment (the use of sealed envelopes or independent researchers). Because of the nature of the interventions, performance bias was high in most studies; only 2 studies [ 41 , 47 ] were assessed as having a low risk of bias in participant blinding due to the use of nonpenetrating SA.…”
Section: Resultsmentioning
confidence: 99%